Analysis of Marketing Kampung Super Strategy in Grobogan District - Sunarti, Dwi; Mulyatno, Bambang; Anindyawati, Elisa (International Journal of Environment, Agriculture and Biotechnology, 2019)
Indonesia's natural wealth is very abundant and various kinds of biodiversity become one of the supporting factors in fulfilling protein needs in the livestock subsector. Farmers choose the type of Super Village Chicken because the harvest period is faster (45-60 days), provides sufficient income, relatively low mortality rates, savings in maintenance and feed costs. The large population of Kampung Super Chicken farms in Grobogan Regency causes breeders difficulties in marketing chicken, so the sale price in the farm is unstable. This price instability does not dare to take larger scale chicken seeds. The method used in this study is the survey method. The number of samples is 60 respondents. The reason for the sample is 60 because there are 6 farmer groups in Grobogan Regency, each with 10 members. Tracer traders use the snow ball method from farmers and the marketing institutions involved. The data analysis included descriptive analysis to determine the business income at the farmer level and SWOT Analysis to find out the Super Village Chicken Marketing Strategy in Grobogan Regency. Based on the results of the discussion, conclusions can be drawn as follows: (1) Marketing efficiency below 50% is said to be efficient, (2) Factors that encourage and inhibit marketing of Super Village Chicken are fluctuating chicken prices, difficult marketing efforts, capital business is relatively limited, lack of knowledge of farmers, (3) Marketing strategy that should be done to improve the marketing of super chicken in Grobogan Regency is to cooperate with other parties in partnership, conduct transactions directly with buyers, make breakthroughs by selling in supermarkets, providing business cutting chicken, selling to big collectors, innovating various chicken products.